THE RELATIONSHIP BETWEEN “ART” AND “LIFE” IN “THE PICTURE OF DORIAN GRAY” BY OSCAR WILDE = MỐI QUAN HỆ GIỮA “NGHỆ THUẬT” VÀ “CUỘC SỐNG” TRONG TÁC PHẨM “THE PICTURE OF DORIAN GRAY” CỦA NHÀ VĂN OSCAR WILDE - Nguyễn, Thị Dung (2020)
The picture of Dorian Gray, the only novel in Oscar Wilde’s writing career, is a valuable work of literature which attracts almost readers as they discover it. The novel reveals a lot of topics to discuss and study such as Dorian Gray’s sins, the fight between the good and the evil or the moral values, etc. When I discover the story, I am really interested in and want to investigate another theme: the relationship between “life” and “art” in the novel. Normally, ‘life” and “art” are considered major parts creating the plot for a work of literature. Hence, I am eager to see how they are presented in Wilde’s novel. To find out the relationship between them, I conduct a research as my thesis entitled The relationship between Life and Art in The Picture of Dorian Gray. In order to fulfill my graduation thesis, I employ the qualitative methodology. The thesis, as such, includes four main parts. The first part is introduction which contains the rationale, aims, significance, methodology, scope and organization of the study. The second part – theoretical background consists of two chapters: chapter one is the brief information about society and history of the nineteenth century, chapter two is the general knowledge of Oscar Wilde’s biography. The third part, also the most important one, is development. This part is divided into three chapters developed from the two former ones: chapter three, four and five. Chapter three deals with the illustration of art in the novel throughout the preface, the portrait of Dorian Gray and Sibyl Vane’s acting. Chapter four surrounds the demonstration of life in the story with the life of the central characters-Dorian Gray and other main ones. The fifth chapter puts emphasis on the relationship between “life” and “art” in The Picture of Dorian Gray. The last part- conclusion summaries all the findings of this research that the author has found and gives some suggestions for further research about this topic as well as the novel. I hope that my thesis will, to some extent, show you the relationship between the “life” and the “art”, how these two elements influences and conflict to each other in the novel. Additionally, this paper wishes to offer you a new investigation into the novel The Picture of Dorian Gray.